2016
DOI: 10.1016/j.jneumeth.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry imaging of rat brain lipid profile changes over time following traumatic brain injury

Abstract: Lipid biochemical and structural changes after TBI could help highlighting molecules that can be used to determine the severity of such injuries as well as to evaluate the efficacy of potential treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 50 publications
5
106
3
Order By: Relevance
“…Roux et al have reported changes in other lipids, from an entire brain tissue section (namely, ceramide, SM, cholesterol derivatives, and other glycerophospholipids, (50 μ m resolution)) at later time points post-TBI using a combined sliver nanoparticle/ion mobility MALDI imaging technique. 44 …”
Section: Resultsmentioning
confidence: 99%
“…Roux et al have reported changes in other lipids, from an entire brain tissue section (namely, ceramide, SM, cholesterol derivatives, and other glycerophospholipids, (50 μ m resolution)) at later time points post-TBI using a combined sliver nanoparticle/ion mobility MALDI imaging technique. 44 …”
Section: Resultsmentioning
confidence: 99%
“…Gold cluster ion currents, although proving the potential of the technique, were insufficient for implantation of the large areas necessary for organ imaging. More recently, an alternative method for homogeneous implantation of metalnanoparticulate ions into tissue enables reproducible MILDI-MS imaging after 500 eV implantation of 8 nm AgNP into heart [5], kidney [6], and brain [7,8] unfixed cryostat sections. In the brain studies, MILDI-MS imaging was used to study injury and pathology in controlled cortical impact [7] and alcoholism [8] using rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting MALDI images, therefore, provide a multilipid spatially unbiased readout of lipid distributions compared with more traditional biochemical analysis of isolated brain regions. Although recent publications have shown the utility of MALDI IMS in assessing changes in lipid distributions in the brain after blast injury 45 and pericontusional changes after CCI, 46 the current study provides early postinjury evidence of altered changes in specific lipids related to LPA and LPA metabolites in both proximal and remote regions of the brain after injury. The most pronounced expression occurred in white matter tracts throughout the brain, including the corpus callosum and the cerebellum.…”
Section: Enhanced Lpa Metabolism As a Potential Marker Of Diaschisis mentioning
confidence: 65%